Pulmonary function test in type 1 diabetics - R.N. Gajbhiye; A.S. Tambe (Al Ameen Medical College, 2013)
Objective: Present study was undertaken to find out the effect of diabetes on the respiratory system. Background: Diabetes is a disease with multiple organ involvement. Glycosylation of tissue proteins occur when blood glucose level remain elevated for a prolonged duration. Due to this, there occur irreversible changes in the chemical structure of tissue proteins. Basement membrane and connective tissues in skin, muscles, respiratory system, vascular bed, kidney, peripheral nervous system, etc. are the targets for glycosylation. Pulmonary function testing (P.F.T.) is a valuable tool for evaluating the respiratory system, representing an important adjunct to the patient history, various lung imaging studies, and invasive testing such as bronchoscopy and open-lung biopsy. Material and Method: 64 type 1 diabetic subjects and 60 controls were selected for the study. Anthropometric parameters, blood investigations and P.F.T. were performed on all subjects. Result and Discussion: Fasting and Post Meal blood glucose levels as well as HbA1c% were significantly higher in type 1 diabetics as compared to controls. All P.F.T. parameters excepting FEV1 % were also significantly reduced in type 1 diabetics. Decreased values of P.F.T parameters in type 1 diabetics can be attributed to biochemical alteration of connective tissue constituents particularly collagen and elastin as well as by microangiopathy due to nonenzymatic protein glycosylation induced by chronic hyperglycemia.